2005
DOI: 10.1103/physrevb.72.134205
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and particle-size dependence of the equilibrium order parameter of FePt alloys

Abstract: First, second and third nearest neighbor pair mixing potentials for equiatomic FePt alloys were calculated from first principles by the Connolly-Williams method within the canonical cluster expansion formalism. It was demonstrated that the Connolly-Williams potentials (based on completely ordered states) and the Korringa-Kohn-Rostoker coherent potential approximation (KKR-CPA) potentials (based on completely disordered state) can be brought into very close correspondence to each other simply by increasing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 53 publications
5
83
2
1
Order By: Relevance
“…The compositions of these particles would place it beyond the bulk compositional phase field for the L1 0 ordering. 16 This composition variation could inhibit the phase transformation and is the subject of further work. Although the total volume fraction of FePt nanoparticles with A1 phase is small, it will give a soft component to the M-H curve as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The compositions of these particles would place it beyond the bulk compositional phase field for the L1 0 ordering. 16 This composition variation could inhibit the phase transformation and is the subject of further work. Although the total volume fraction of FePt nanoparticles with A1 phase is small, it will give a soft component to the M-H curve as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Relevant information about structural stability and electronic properties of the Fe-Pt nanoclusters have been obtained by the theoretical studies based on either semiempirical potentials or ab initio techniques. [22][23][24][25][26][27] The Monte Carlo simulations showed that a continuous transformation between the ordered structure L1 0 (tP4) and a disordered phase in Fe-Pt NPs occures at temperatures lower than the bulk melting temperature (1572 K). 23,24 Disordering processes in nanoalloys are enhanced due to finite-size and surface effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon has been explained with size, kinetic, and surface segregation effects. [7][8][9][10][11][12][13] One of the possible approaches to achieve high L1 0 order and a correspondingly high magnetic anisotropy is by doping FePt nanoparticles with a third element. 1,3 Atomic species such as Ag, [14][15][16][17][18][19][20] Au,17,[19][20][21][22][23][24][25] and Cu 25-27 have been previously tested.…”
mentioning
confidence: 99%